2020
DOI: 10.1002/oby.22954
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Obesity as a First Step to Weight Loss: An Observational Study

Abstract: Objective: This study aimed to explore the relationship between an obesity diagnosis and weight loss as a percentage of total body weight loss over 9 to 15 months, using electronic health record data. Methods: An observational study of 688,878 adult patients at 15 health systems with BMI ≥ 30 kg/m 2 examined the relationship between weight loss and documentation of obesity diagnosis. Multivariable logistic regression models were created using a stepwise backwards elimination procedure to identify potential pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…A formal diagnosis was viewed as the first step toward changing provider and patient behaviors in terms of addressing obesity, and there is evidence to support this. 14 Documentation of an obesity diagnosis was defined as an active obesity diagnosis code on the patient's problem list in the EHR or on a claim for a visit during the reporting period, among all patients with a BMI ≥30 kg/m 2 . This measure was evaluated preliminarily as a quality performance measure, as recommended by the NQF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A formal diagnosis was viewed as the first step toward changing provider and patient behaviors in terms of addressing obesity, and there is evidence to support this. 14 Documentation of an obesity diagnosis was defined as an active obesity diagnosis code on the patient's problem list in the EHR or on a claim for a visit during the reporting period, among all patients with a BMI ≥30 kg/m 2 . This measure was evaluated preliminarily as a quality performance measure, as recommended by the NQF.…”
Section: Methodsmentioning
confidence: 99%
“… 12 Other potential measures include documentation of a diagnosis of obesity; prescription for, or referral to, an evidence-based treatment or program; and change in quality of life (QOL) as assessed by patient-reported outcome measures (PROMs). 11 The documentation of an obesity diagnosis has, in fact, been associated with self-reported, 13 as well as electronic health record (EHR)-derived, 14 weight loss success. Improvements in BMI and waist circumference 15 and long-term weight loss 16 in adults have been correlated with improved health-related QOL.…”
Section: Introductionmentioning
confidence: 99%
“…The liver is a major target organ of toxicity and its injury affects the integrity of hepatocytes causing the release of membrane bound enzymes (e.g., ALT and AST), destroy hepato-biliary system thereby leading to the release of essential enzymes (e.g., ALP) [41,42]. In the current study, no significant differences were observed in serum ALT, AST and ALP levels between treated and untreated groups after oral administration of 1/10 LD50 of P. roxburghii or N. graveolens extracts.…”
Section: Chronic Toxicity Trailmentioning
confidence: 99%
“…Establishing trust and open communication between the provider and patient is essential to understanding these differences in beliefs and expectations. The observation that patients who receive a diagnosis of obesity are more likely to engage in weight management compared with their undiagnosed peers emphasizes the importance of the patient‐provider relationship (13). After obesity is diagnosed, shared decision‐making is vital to the obesity treatment process.…”
Section: Introductionmentioning
confidence: 99%